Refractory Ileal Perforations in a Cytomegalovirus-Infected Premature Neonate Resolved After Ganciclovir Therapy - Mari Morimoto; Hirofumi Sawada; Hirofumi Sawada; Noriko Yodoya; Hiroyuki Ohashi; Kuniaki Toriyabe; Ryo Hanaki; Katsumi Sugiura; Hidemi Toyoda; Kohei Matsushita; Yuhki Koike; Kohei Otake; et al. (Frontiers Media S.A., 2020)
Severe neonatal gastrointestinal diseases such as necrotizing enterocolitis or spontaneous intestinal perforation are potentially lethal conditions which predominantly occur in preterm infants. Cytomegalovirus (CMV), which is known to cause congenital and acquired infections in the newborns, has also been implicated in such severe gastrointestinal diseases in premature infants. However, the pathogenic role of CMV and effect of antiviral therapy in severe gastrointestinal disease in premature neonates is currently unclear. We present an infant, born at 26-weeks' gestation, presented with progressive dyspepsia and abdominal distention after the closure of the symptomatic patent ductus arteriosus at the day of life (DOL) 4, requiring the emergent surgery for ileal perforation at the DOL8. After the surgery, abdominal symptoms persisted and the second emergent surgery was performed for the recurrent ileal perforation at DOL17. Even then the abdominal symptoms prolonged and pathological examination in the affected intestine at the second surgery showed CMV inclusion body. Immunoreactivity for CMV antigen was detected in the specimen at the first surgery on DOL8. Blood and urinary CMV-DNA were detected at DOL28. CMV-DNA was also detected in the dried umbilical cord which was obtained within a week from birth. A 6-week course of intravenous ganciclovir (12 mg/kg/day) was started at DOL34 and then symptoms resolved along with decreasing blood CMV-DNA. Pathological findings characteristic of CMV were not detected in the resection specimen at the ileostomy closure at DOL94. These observations indicate that anti-CMV therapy may be beneficial for some premature infants with severe CMV-associated gastrointestinal diseases and warrants further studies focusing on pathogenic role, diagnosis, treatment and prevention of this underrecognized etiology of severe gastrointestinal diseases particularly in premature neonates.